2018
DOI: 10.1136/bmj.k2649
|View full text |Cite
|
Sign up to set email alerts
|

Strengthening the capabilities of families and communities to improve child health in low and middle income countries

Abstract: Audrey Prost and colleagues discuss how best to enable families and communities to improve child health

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…Egypt and Tanzania have successfully allocated a separate funding stream for IMCI within all district budgets to ensure sufficient and reliable funding of program activities [11]. The health system must also consider the importance of legitimacy and ownership at district level [58][59][60]. In Nepal and Democratic Republic of Congo (DRC), strengthening district health capacity has been an integral part in reaffirmation of IMCI and prevents donor-driven re-prioritization [58].…”
Section: Discussionmentioning
confidence: 99%
“…Egypt and Tanzania have successfully allocated a separate funding stream for IMCI within all district budgets to ensure sufficient and reliable funding of program activities [11]. The health system must also consider the importance of legitimacy and ownership at district level [58][59][60]. In Nepal and Democratic Republic of Congo (DRC), strengthening district health capacity has been an integral part in reaffirmation of IMCI and prevents donor-driven re-prioritization [58].…”
Section: Discussionmentioning
confidence: 99%
“…Meta-analysis of trials leading to a formal guideline from WHO has shown that community mobilisation through women’s groups and participatory learning and action cycles can substantially improve newborn survival in marginalised and rural communities. 8 …”
Section: Unicef-who Leadership Strategy: Five Key Areasmentioning
confidence: 99%
“…These include home visits, women’s groups, community discussion and health committees. 14 However, practice has not matched the increasing evidence, which requires sustained funding and coordination of country-led planning, processes that may be supported by a global re-emphasis on community engagement. Global child health strategies have rarely extended to collaboration with private healthcare providers, even though most children receive private healthcare in many countries.…”
Section: Findings and Insights Into Improving Child Health Strategiesmentioning
confidence: 99%